Sanro: The Contestation of Traditional Medicine with the Modern Health Regime in Jalangnge, Barru Regency, Indonesia - ., Najamuddin; ., Bahri; Tamrin, Sopian; Indarwati, Khofipa (KnE Social Sciences, 2024)
Development in the field of science and technology has driven advancements in medical treatment. However, these advancements do not necessarily diminish the existence of local medicine. As seen in Jalange, Barru Regency, Indonesia, Sanro medicine persists as a traditional treatment alongside modern medical civilization. This research employs a historical-discontinuous approach using Michel Foucault’s concept of the archaeology of knowledge. Data is collected through heuristic, interpretation, historiography, and criticism stages, with a focus on the years 2005 to 2021. The study reveals that Sanro medicine in the Jalange community contests modern medicine, existing through the discourse of local knowledge as its foundation. The treatment methods employed vary depending on the type of disease. Disease names are understood within their community texts, such as Bempalureng, Sarampa, Puru-puru Api (a category of skin diseases that frequently affect the local community), difficulties in childbirth, toothache, and Co’Coereng (accompanied by supernatural beings). Healing is performed through prayers in the Bugis language and the Qur’an, sometimes utilizing water as a medium. Water that has been blessed through prayer is believed to be a source of blessings and healing. Additionally, Sanro practitioners possess herbal concoction skills and employ physical touch, such as applying pressure to the patient’s nerve points. Through these healing practices, Sanro medicine can contest the discourse of modern knowledge while maintaining local culture in the Jalange community of Barru Regency, Indonesia. Keywords: Sanro, contest, local medicine